One-step hysteroscopic myomectomy using Lin dissecting loop and Lin myoma graspers - Bao-Liang Lin; Takayuki Higuchi; Akira Yabuno; Kana Kashinoura; Takeshi Suzuki; Seon-Hye Kim; Sokichi Iwata; Yun Zhao (Wolters Kluwer Medknow Publications, 2012)
Objective: To evaluate the efficacy of hysteroscopic myomectomy using the Lin dissecting loop and Lin myoma graspers to remove myoma in a single procedure. Materials and Methods: This was a retrospective study performed in the gynecologic department of a general hospital. A total of 1569 women with submucous myoma or symptomatic intramural myoma underwent one-step resectoscopic myomectomy using Lin dissecting loop and Lin myoma graspers. Results: Of the 1569 patients, pedunculated submucous myoma, sessile submucous myoma, and intramural myoma were diagnosed in 943, 608, and 19 patients, respectively. The patients' median age was 38.6 years (range 19-59 years). The operating time was between 4 minutes and 147 minutes (mean 30.6±18.2 minutes). The specimen weighed from 0.1 g to 380 g (mean 19.9±21.4 g). Two uterine perforations caused by myoma graspers were encountered. No fluid complications were experienced. Almost all of the patients had improvement of symptoms. Long-term follow-up revealed five cases of abdominal total hysterectomy, one case of abdominal myomectomy, 21 cases of rehysteroscopic operation, 59 cases of normal spontaneous delivery, 36 cases of cesarean section, five cases of ongoing pregnancy, and one case of spontaneous abortion. No case of uterine rupture was encountered. There was one case of placenta accreta that required hysterectomy. Conclusion: Using our technique and instruments, it is possible to remove a myoma in a single procedure safely and effectively. This surgical method can also preserve more endometrium, cause less injury to the muscle layer, and prevent fluid complications.